Application of Reverse Engineering method to model eroded Francis runner. (August 2020) - Sedai, Ashish; Thapa, Biraj Singh; Thapa, Bhola; Kapali, Aman; Qian, Zhongdong; Guo, Zhiwei
Abstract: Damage of runners and other components of hydro turbine by sediment erosion and cavitation erosion is an inevitable problem associated with hydropower established in a region with mountainous topology. The paper attempts to investigate the suitability and sustainability of the reverse engineering method for the design of the eroded Francis runner. This manufacturing technology is in a progressive phase of development in various parts of the world, so research scholars have been constantly working on the concept to increase the speed and efficiency of the method. The case investigation was conducted on Puwa-Khola 1HPP eroded Francis runner. The paper investigates reverse engineering design methodology of the eroded runner and discusses scope and limitation in the utilization of method at Hydropower sector. Also, the paper suggests suitable 3D scanning techniques, reverse engineering tools, and optimization methods for obtaining mathematically sound models without any hydraulic profile deviation between actual and reversed engineered model.